Rapid diagnosis of duck Tembusu virus and goose astrovirus with TaqMan-based duplex real-time PCR - Li, Haiqin; Wan, Chunhe; Wang, Zhangzhang; Tan, Jia; Tan, Meifang; Zeng, Yanbing; Huang, Jiangnan; Huang, Yu; Su, Qi; Kang, Zhaofeng; Guo, Xiaoquan (Frontiers in Microbiology, 2023)
The mixed infection of Tembusu virus and goose astrovirus is an important problem that endangers the goose industry, but there is no reliable method to detect these two pathogens at the same time. In this study, by analyzing the published genomes of Tembusu virus and Goose Astrovirus, we found that both viruses have high conservation, showing 96.5% to 99.5% identities within different strains. Subsequently, PCR primers and Taqman probes were designed to identify Tembusu virus and Goose Astrovirus, and different fluorescent reporters were given to two probes for differential diagnosis. Through the optimization and verification, this study finally developed a multiplex Taqman qPCR method that can simultaneously detect the above two viruses. The lower limits of detection were 100 copies/μL and 10 copies/μL for DTMUV and GoAstV. This method has high sensitivity and specificity, and provides a method basis for clinical prevention and control of these two viruses.